Discourses of Cultural Relevance in Nunavut Schooling - M. Lynn Aylward (Journal of Research in Rural Education, 2007)
Academic discourse relating to the cultural relevance of indigenous education is ever expanding both nationally in Canada and internationally. Refl ecting upon recent research data as well as lived experience as a teacher educator in Nunavut, I offer a critique of some well-established beliefs connected to considerations of culturally appropriate schooling within indigenous school contexts. Specifi cally, the relationships between cultural relevance and sameness, place and community are explored in a discussion of educational change within the Canadian arctic territory of Nunavut.